Morphometric analysis of Malaysian Oxudercine goby, Boleophthalmus boddarti (Pallas, 1770) - Daud, Siti Khalijah; Mohammadi, Mehdi; Siraj, Siti Shapor; Zakaria, Mohamad Pauzi (Universiti Putra Malaysia Press, 2005)
The Oxudercine gobies or mudskippers are locally known as belacak or "tembakul". These euryhaline fish are amongst the air breathing gobies found in Malaysia. Boleophthalmus boddarti is one of the common mudskippers inhabiting tidal flats, mangrove swamps, estuarines and coastal areas. Conventional and truss morphometrics as well as meristic data from 85 samples in five populations (Pulau Pinang, Kuala Selangor, Banting, Port Dickson and Melaka) of B. boddartiwere analyzed using one-way ANOVA and Principal Component Analysis (PCA). Fifteen morphometric, 28 truss morphometric and 9 meristic data were analyzed to examine the degree of similarity among the five populations. All morphometric characters within and between the populations were significantly different (P< 0.05). Using the conventional morphometric data analysed by PCA, the populations of B. boddarti are clustered into 3 groups, where Banting andMelaka populations form the first group, Pulau Pinang and Kuala Selangor populations the second group and Port Dickson population the third group. In contrast, 3 groups were also clustered based on the truss morphometric data but the grouping was different. The three groups from the truss morphometric data consist of Kuala Selangor and Banting populations in the first group, Melaka and Port Dickson populations the second group and the Pulau Pinang populationthe third group which is distantly separated from the other two groups. The results indicate that the shape of mudskippers in the northern part is distinct from the middle and southern parts of Peninsular Malaysia. Based on meristic data, all populations were centric and no grouping was identified. The length-weight relationship for B. boddarti in this study was described as log W=log 0.754 + 1.029 log TL.